2020
DOI: 10.1073/pnas.1920244117
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structures of cyanobacterial light-dependent protochlorophyllide oxidoreductase

Abstract: The reduction of protochlorophyllide (Pchlide) to chlorophyllide (Chlide) is the penultimate step of chlorophyll biosynthesis. In oxygenic photosynthetic bacteria, algae, and plants, this reaction can be catalyzed by the light-dependent Pchlide oxidoreductase (LPOR), a member of the short-chain dehydrogenase superfamily sharing a conserved Rossmann fold for NAD(P)H binding and the catalytic activity. Whereas modeling and simulation approaches have been used to study the catalytic mechanism of this light-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 61 publications
3
61
0
Order By: Relevance
“…However, in the absence of crystal structures, the authors presented a model of the structural change involving rigidification of a C‐terminal extension of the protein. A recent crystal structure of POR suggests that the lid regions formed an interface between two POR monomers, although it is not clear if this was an artefact of the crystallisation process [27]. The studies described here support the idea that Pchlide binding leads to a more rigid protein.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…However, in the absence of crystal structures, the authors presented a model of the structural change involving rigidification of a C‐terminal extension of the protein. A recent crystal structure of POR suggests that the lid regions formed an interface between two POR monomers, although it is not clear if this was an artefact of the crystallisation process [27]. The studies described here support the idea that Pchlide binding leads to a more rigid protein.…”
Section: Discussionsupporting
confidence: 60%
“…We have shown that two lid regions located in the distal region of the active site are important for oligomerisation and photocatalysis. These lid regions are inherently flexible and adopt multiple conformations in the absence of substrate [26,27]. This mobility in the apo-enzyme likely disfavours interaction with lid regions of other POR monomers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To understand the effect of Pchlide and MGDG binding on LPOR, we compared our structure to the Pchlide-free, NADPH-bound cyanobacterial LPORs 6,14 (Fig. 3d, Fig.…”
Section: Pchlide Induces Atporb Conformational Changes That Promote Imentioning
confidence: 99%
“…The catalytic YxxxK and the NADPH-bounding G-rich (GxxxGxG) motifs are conservative (Wilks and Timko, 1995 ; Schoefs and Franck, 2003 ; Gabruk and Mysliwa-Kurdziel, 2020 ). LPOR crystal structure remained unknown for a long time; the structures of two cyanobacterial LPOR enzymes have been published only recently (Zhang et al, 2019 ; Dong et al, 2020 ). In general, both structures are compatible with the homology models, however, due to slightly different protocols there were some differences between these two works.…”
Section: Lpor—an Enzyme Operating In Lipid Environmentmentioning
confidence: 99%